STUDENTS’ PERCEPTIONS OF THE USE OF ORAL PRESENTATION AS A METHOD OF LEARNING - Cempaka, Adisti Gilang; Anjanie, Anjanie (Jurnal Ekonomi dan Bisnis, 2020)
The concept of active learning encourages students’ autonomy and their ability to learn and helps students to become "lifelong learners". Oral presentation method is considered as one of the methods that can encourage student’s active learning. The purpose of this study is to identify students’ perceptions of the application of oral presentation method in learning process. The data was collected using questionnaire survey with 39 respondents from Financial Statement Analysis course participated in this study. The results of this study indicate respondents’ positive perception of the use of oral presentation as a method of learning. The respondents appreciated the use of oral presentation since the method is beneficial to stimulate them to be an active learner.